The Role of Non-Governmental Organisations in Poverty Resolution in Bandung City with a Sustainable Development Goals Approach: NGO Case Study Bantu Teman Id - Nugraha, Satria Adi; Wilodati; Asyahidda, Fajar Nugraha (International Journal of Science and Society, 2024)
This research analyzes the role of Non-Governmental Organizations (NGOs) in dealing with poverty in Bandung City by applying the Sustainable Development Goals (SDGs) approach. The research was conducted using a qualitative research approach, involving in-depth interviews, participant observation, and document analysis. The focus of this research is to understand the concrete contributions and impacts produced by various programs and initiatives carried out by NGOs in the city of Bandung. The results of the research show that NGOs play a crucial role in poverty alleviation efforts. Community economic empowerment, inclusive education, access to health, and improving urban infrastructure are at the core of NGO contributions. Economic empowerment programs have proven effective in increasing the economic capacity of low-income communities. Inclusive education programs provide better access and improve the quality of education, while public health efforts have succeeded in increasing the level of health and welfare of the community. This research concludes that through the SDGs approach, NGOs in Bandung City not only function as development actors but also as catalysts for social change. Research findings provide concrete evidence that various programs and initiatives carried out by NGOs have a measurable positive impact in overcoming poverty at the local level. NGOs' active involvement with local communities, regional governments and the private sector also proves the importance of cross-sector collaboration to achieve sustainable development goals. The success of NGOs in helping overcome poverty in Bandung City highlights their potential role in continuing the sustainable development agenda. This research contributes to our understanding of how implementing the SDGs through concrete NGO actions can have a positive and sustainable impact at the local level. The policy and practical implications of these findings are the importance of supporting and strengthening the role of NGOs as strategic partners in achieving sustainable development goals, especially in the context of overcoming poverty in developing cities such as Bandung City.